2015
DOI: 10.1080/1047840x.2015.992677
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Elements of Psychological Resilience: An Integrative Framework for the Study of Individuals, Families, and Communities

Abstract: Psychological resilience has become a popular concept. Owing to that popularity, the word resilience has taken on myriad and often overlapping meanings. To be a useful framework for psychological research and theory, the authors argue, the study of resilience must explicitly reference each of four constituent temporal elements: (a) baseline or preadversity functioning, (b) the actual aversive circumstances, (c) postadversity resilient outcomes, and (d) predictors of resilient outcomes. Using this framework to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
438
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 405 publications
(501 citation statements)
references
References 266 publications
22
438
0
6
Order By: Relevance
“…The present study corroborates a number of studies which indicate significant prediction of individual resilience by demographic characteristics: age, gender and economic condition [17,[56][57][58]; community type, age, and levels of religiosity and preparedness, predicting community and national resilience [29,52]; level of exposure and individual resilience [17]. Our result has indicated that these four demographic variables and exposure examined in our study explained 27% of individual resilience SVR.…”
Section: Discussionsupporting
confidence: 80%
“…The present study corroborates a number of studies which indicate significant prediction of individual resilience by demographic characteristics: age, gender and economic condition [17,[56][57][58]; community type, age, and levels of religiosity and preparedness, predicting community and national resilience [29,52]; level of exposure and individual resilience [17]. Our result has indicated that these four demographic variables and exposure examined in our study explained 27% of individual resilience SVR.…”
Section: Discussionsupporting
confidence: 80%
“…Bonanno (2005) has defined individual resilience as the individual's ability to maintain a stable level of functioning following traumatic events and as a "trajectory of healthy functioning across time" (p. 136). Bonanno and associates have argued further that most people display a high level of resilience after a PTE (Bonanno, Romero & Klein, 2015). Most studies on resilience have focused on individual resilience and have indicated that it is a key issue in buffering negative psychological consequences of major adversities (Suedfeld, 2015).…”
Section: Psychological Resiliencementioning
confidence: 99%
“…Resilience indicators can be based on self-report tools as well as on measuring various actual behaviors at different times after the PTE has taken place (Bonanno, 2004;Bonanno, Romero & Klein, 2015). (b) Resilience predictors are based on measures taken before a potential traumatic event has taken place and are mostly based on self-report tools (e.g., Kimhi & Eshel, 2015).…”
Section: Psychological Resiliencementioning
confidence: 99%
“…Therefore, having low resilience at some time does not preclude the presence of future resilience or vice versa. Consequently, it is important to study adolescent resilient functioning, and its influences, over time (Bonanno et al 2015). Understanding how adolescent resilient functioning varies over time and revealing how various factors influence such variation remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%